2016
DOI: 10.1590/1807-3107bor-2016.vol30.0046
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infection spread through saliva – a truth or myth?

Abstract: In this Point-of-view article we highlighted some features related to saliva and virus infection, in special for zika virus. In addition, we pointed out the potential oral problems caused by a microcephaly originated by a zika virus infection. In the end the, we demonstrated the importance of a more comprehensive exploration of saliva and their components as a fluid for diagnostic and therapeutic approaches on oral and systemic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
(17 reference statements)
1
17
0
5
Order By: Relevance
“…According to a previous study on vesicular stomatitis virus, this pathogen has a strong aggregating ability in the presence of saliva, and some host factors, such as fibrinogen, could promote this saliva-induced aggregation process, suggesting the important role saliva plays in the biological behavior of this virus (Anschau & Sanjuan, 2020). According to another study, the biochemical components of saliva are closely associated with the presence of Zika virus (ZIKV), indicating complex interactions between the virus and saliva (Siqueira, Moffa, Mussi, & Machado, 2016). Hence investigation of the biological functions of saliva on the behavior of viruses, and the impact of virus on the composition of saliva, suggest the transmission of virus can be closely connected with saliva.…”
Section: Saliva a S A P Otential Source Of Virus S Pre Admentioning
confidence: 99%
“…According to a previous study on vesicular stomatitis virus, this pathogen has a strong aggregating ability in the presence of saliva, and some host factors, such as fibrinogen, could promote this saliva-induced aggregation process, suggesting the important role saliva plays in the biological behavior of this virus (Anschau & Sanjuan, 2020). According to another study, the biochemical components of saliva are closely associated with the presence of Zika virus (ZIKV), indicating complex interactions between the virus and saliva (Siqueira, Moffa, Mussi, & Machado, 2016). Hence investigation of the biological functions of saliva on the behavior of viruses, and the impact of virus on the composition of saliva, suggest the transmission of virus can be closely connected with saliva.…”
Section: Saliva a S A P Otential Source Of Virus S Pre Admentioning
confidence: 99%
“…Recent findings have shown that ZIKV can be detected in the saliva of infected mothers and their neonates, but until now, there has been no evidence that ZIKV can be transmitted through human saliva (Siqueira, Moffa, Mussi, & Machado, ). A recent outbreak of ZIKV occurred in Latin America.…”
Section: Anti‐viral Effects Of Lf and Lf‐derived Peptidesmentioning
confidence: 99%
“…Mutations in COL1A1/2 genes were associated with congenital brittle bones with the development of microcephaly and cataracts, as observed in the most severe cases of CSZ 40 . A dominant mutation in COL12A1 was also related to joint laxity 41 , a phenotype often found in ZIKV-infected children 42 .…”
Section: Discussionmentioning
confidence: 90%